Public Health Surveillance Toolkit : A Guide for Busy Task Managers - Garcia-Abreu, Anabela; Halperin, William; Danel, Isabella (World Bank, Washington, DC, 2014)
This toolkit draws on the expertise of public health practitioners who have experience with public health surveillance and who have recognized the core role of surveillance in public health. These practitioners have advocated for surveillance programs, supplied innovative ideas, and provided insightful critiques over many years. This toolkit also draws on the experience of Bank staff and technical experts from the PAHO and the CDC who have contributed to Bank missions. The toolkit also makes use of WHO references, primarily those from the WHO s Web site. Part A of this toolkit provides some theoretical concepts, and knowledge about surveillance that has been gained through applying these concepts and the practice of surveillance in developing countries. Part B provides information that will be useful to Task Managers as they prepare loans for strengthening public health surveillance systems. Several World Bank experiences are shared. The focus of part B is on practical aspects of surveillance and on lessons learned.